Letter (copy) : Basque children - Tewson, Vincent
037-0147-001 HVT/EK/1044. Secretary's. 5th June, 1937. Mrs. E.L. Poland, Worthing Labour Party, Women's Section, 45, Meredith Road, WORTHING. Dear Mrs. Poland, BASQUE CHILDREN. Many thanks for your letter of the 3rd instant. I quite appreciate what you say and as you are already assisting in the support of sixty children in Worthing you cannot be expected to do more than this. Yours sincerely, Assistant Secretary. 292/946/37/147